Effect of The Water Origin on The Biological Properties of Sage (Salvia officinalis L.) Aqueous Extracts - Irina Korotkova; Tamila Romashko; Oleg Khakhel'; Tamila Zvenihorodska; Tetiana S Yaprynets; Viktor Liashenko (Pandawa Institute, 2025)
Plant extracts, due to the high content of various biologically active compounds, have found their wide application in the foods, pharmaceutical industries, and agricultures, for the production of valuable and useful bioproducts. The aqueous plant extracts are most often used. The effect of the water origin used in their preparation on the extract’s composition has not been studied enough, which limits their use. The study was aimed to compare the biological effect of sage (Salvia officinalis L.) extracts prepared using water of different origins (distilled, tap, spring, bottled). The preparation of aqueous extracts was carried out in two ways, differing in the extraction temperature. In the first method, boiling water was used to prepare the extract; in the second, cooled boiled water was used. The sage leaves mass for extract preparation was 1.65 and 3.30 g. The biological activity of the extracts was assessed by testing them for radish germination. It was shown the sage leaves extracts prepared using various waters origin can differ by one and half times in their allelopathic effect on radish seeds. It was proved the qualitative composition and mass of the substance extracted from the plant depend on the water origin used for extracts preparation. Thus, using the same amount of plant material to prepare extracts, you can increase their biological activity by fifty percent with the right choice of water.